DUAL-QUANTUM CHANNEL KEY DISTRIBUTION MODEL USING DUAL BINARY SEQUENCE - HONG , KAH WING (2019)
The rapid growth of advanced technology has fueled the rise of cybercrime that is becoming increasingly complicated to detect, combat and mitigate. Over the past three decades, the quantum properties of light and matter have been applied to the field of information security.